Impact of Diversity Management Against Employee Engagement: in B2B Companies - Tantri Yanuar Rahmat Syah*; Diah Ayu Ambarini; Rojuaniah Rojuaniah; Ikramina Larasati Hazrati Havidz; Fadilah Nur Azizah (Universitas Syiah Kuala, 2023)
Diversity management can be considered differences related to gender, ethnicity, age, religion, sexual orientation, physical abilities, or other sources of differences that can have a significant impact on employee engagement. The emotional relationship of employees with organizational involvement and workplace diversity management positively affects employee improvement. This study aims to describe and explain the application of diversity management to achieve a competitive advantage at PT. Pratita Prama Nugraha. This study also aims to determine the mediating role of organizational trust in the relationship between diversity management and employee engagement at PT. Pratita Prama Nugraha. This study used a purposive sampling method involving 120 B2B company employees. Data were analyzed using Structural Equation Model (SEM) with SmartPLS 3.0. The results of the empirical analysis prove that the significant influence of diversity management has no effect on employee engagement but has a positive effect on organizational trust and affective commitment. The results from other studies indicate that organizational trust can be considered a mediating variable between diversity management and employee engagement